Enhancing Ocean Economy Growth for Regional Development in the Special Region of Jakarta, Indonesia - Harun Idham Akbar; Tridoyo Kusumastanto; Ario Damar Damar; Wiwin Ambarwulan Ambarwulan; Kastana Sapanli (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2026)
The ocean economy plays a crucial role in driving regional development and sustainable natural resource management, particularly in metropolitan coastal areas such as the Special Region of Jakarta (Daerah Khusus Jakarta, DKJ). Despite the rapid development of the ocean economy in many regions, there is little comprehensive research on the ocean economy at the metropolitan scale.This work applies to an Input-Output approach to assess the ocean economic activity within the DKJ area, relying on a regional IO matrix from 2016. Alongside come figures on Gross Regional Domestic Product (GRDP), employment creation factors, and measures of influence spread across industries. Emphasis emerges where certain fields show notable interdependencies with marine-relatedoutputs, shaping paths for advancement. Through such patterns, attention shifts naturally toward those branches capable of generating wider ripple effects. The results show that 25% of DKJ's total output comes from the ocean economy, accounting for 19.7% of the province’s GRDP in 2016. By 2024, GRDP from the ocean economy reached IDR 721 trillion, with projected output of IDR 1,805 trillion. The two largest contributors are marine construction and marine tourism, followed by the maritime industry and the transportation sectors. Where complex logistics chains are examined, integrated approaches like Blue Urbanism emerge, linking constructed spaces to renewed ecosystems. Within different areas, port networks operate independently yet grow tightly linkedunder this framework. Evidence gathered supports detailed planning methods aimed at shaping coastal urban economies where industry expands steadily alongside ecological care and fairer community outcomes.